Scope and challenges of introducing sustainable procurement in Power grid Company of Bangladesh Ltd. (PGCB Ltd.) - Ashraf, Sadat Bin (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.